The Analysis of Personal Branding of People with Tattoos - Joshua Nathan Davies (Universitas Syiah Kuala, 2023)
The practice in body modification has been around for thousands of years, especially the practice of tattooing. With modern technology, the number of people getting tattoos is increasing drastically and their reason has become more meaningful than ever. Using tattoos as a form of personal branding has become a new phenomenon in today’s modern age. They have become a form of communication used to express who they are as a person. This research looks into how people create a personal brand for themselves using a medium like tattoos. The theory used in this research is the Eight Step Program Theory by Peter Montoya, which is a process theory designed to help create and plan a personal brand to target specific target audiences. This study and research uses a qualitative methodology which integrates both primary and secondary data sources. It also uses a case study method to research and analyze the information gathered from its primary informants. The results of this study show that personal branding with tattoos primarily consists of people using experiences in their life, or certain values they have about themselves to brand themselves with, also it can be an effective way of communicating a message about yourself. The study also found that to guarantee message success, one must pay close attention to design and location of the tattoo. The study also found that Montoya’s Theory is suitable for someone trying to personally brand themselves with tattoos.